Assessment of Lentiviral Vector Mediated CFTR Correction in Mice Using an Improved Rapid in vivo Nasal Potential Difference Measurement Protocol - Cmielewski, P.; Delhove, J.; Donnelley, M.; Parsons, D. (Frontiers in Pharmacology, 2021)
Cystic Fibrosis (CF) is caused by a defect in the CF transmembrane conductance regulator (CFTR) gene responsible for epithelial ion transport. Nasal potential difference (PD) measurement is a well-established diagnostic technique for assessing the efficacy of therapies in CF patients and animal models. The aim was to establish a rapid nasal PD protocol in mice and quantify the efficacy of lentiviral (LV) vector-based CFTR gene therapy. Anaesthetised wild-type (WT) and CF mice were non-surgically intubated and nasal PD measurements were made using a range of buffer flow rates. Addition of the cAMP agonist, isoproterenol, to the buffer sequence was then examined. The optimised rapid PD technique was then used to assess CFTR function produced by second and third generation LV-CFTR vectors. V5 epitope tagged-CFTR in nasal tissue was identified by immunohistochemistry. When intubated, mice tolerated higher flow rates. Isoproterenol could discriminate between WT and CF mice. Improved chloride transport was observed for the second and third generation LV-CFTR vectors, with up to 60% correction of the cAMP-driven chloride response towards WT. V5-CFTR was located in ciliated epithelial cells. The rapid PD technique enables improved functional assessment of the bioelectrical ion transport defect for both current and potential CF therapies.